2016
DOI: 10.5194/acp-16-12273-2016
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of horizontal and vertical transport of water in the Southern Hemisphere tropical tropopause layer (TTL) from high-resolution balloon observations

Abstract: Abstract. High-resolution in situ balloon measurements of water vapour, aerosol, methane and temperature in the upper tropical tropopause layer (TTL) and lower stratosphere are used to evaluate the processes affecting the stratospheric water budget: horizontal transport (in-mixing) and hydration by cross-tropopause overshooting updrafts. The obtained in situ evidence of these phenomena are analysed using satellite observations by Aura MLS (Microwave Limb Sounder) and CALIPSO (Cloud-Aerosol Lidar and Infrared P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 52 publications
6
21
0
Order By: Relevance
“…The largest errors are however localized in space and time, as they occured in episodes, over regions where wind observations are exremely sparse (Indian Ocean, eastern Pacific Ocean). This is not incompatible with previous case studies which convincingly showed, using complementary observations of water vapor in particular, trajectory calculations which provided insight on injection and transport of water vapor in the UTLS ( [14,15], and B. Legras and S. Bucci, personal communication). Our results nonetheless emphasize the need for continued efforts to better understand processes and model error in the UTLS near the Equator, and to pay particular attention to uncertainties in trajectory calculations in process studies.…”
Section: Discussionsupporting
confidence: 81%
“…The largest errors are however localized in space and time, as they occured in episodes, over regions where wind observations are exremely sparse (Indian Ocean, eastern Pacific Ocean). This is not incompatible with previous case studies which convincingly showed, using complementary observations of water vapor in particular, trajectory calculations which provided insight on injection and transport of water vapor in the UTLS ( [14,15], and B. Legras and S. Bucci, personal communication). Our results nonetheless emphasize the need for continued efforts to better understand processes and model error in the UTLS near the Equator, and to pay particular attention to uncertainties in trajectory calculations in process studies.…”
Section: Discussionsupporting
confidence: 81%
“…The target convective overshoots and the moistened TTL were simulated using the non-hydrostatic numerical research model, Meso-NH (Lac et al, 2018). For a fine-scale analysis, the simulation uses about 400 million grid points with horizontal grid spacing of 2.5 km.…”
Section: Cloud-resolving Numerical Simulationmentioning
confidence: 99%
“…Cross-tropopause convection provides a means of rapidly transporting boundary layer air into the lower stratosphere, thus bypassing the dominant global-scale troposphere-to-stratosphere transport mechanism associated with the Brewer-Dobson circulation in which air ascends slowly across the tropical tropopause and then moves poleward and descends. Observational and modeling studies indicate that convective overshooting moistens the lower stratosphere through the lofting of ice crystals into the stratosphere, which then subsequently sublimate (Corti et al, 2008;de Reus et al, 2009;Hanisco et al, 2007;Hassim & Lane, 2010;Hegglin et al, 2004;Homeyer, 2014;Homeyer et al, 2017;Iwasaki et al, 2010;Iwasaki et al, 2012;Khaykin et al, 2009;Khaykin et al, 2016;Phoenix et al, 2017;Poulida et al, 1996;Randel et al, 2012;Ray et al, 2004;Sang et al, 2018;Sargent et al, 2014;Sayres et al, 2010;Smith et al, 2017;Wang et al, 2011;Weinstock et al, 2007). Analysis of water and its heavy isotopologue, HDO, indicates that up to 45% of water vapor in the NAMA may be attributed to convective transport of water-predominantly as ice-into the UTLS, though the convective source may not be entirely local (Hanisco et al, 2007;Randel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%